Self-Management of Patients with Diabetes Mellitus: An Integrative Literature Review - Chatarina Hatri Istiarini (Humanistic Network for Science and Technology (HNST), 2018)
A condition where body’s ability in responding insulin is decreasing or pancreascannot produce insulin causes hyperglycemia in clients with DM. Many studies have been done related to self-management of patients with DM. Self-management of Patients with DM needed a literature study to determine the results of one study with another so that it can be a guide in making decisions in performing nursing interventions in patients with DM related selfmanagement. The purpose of this article was identified the evidence-based nursing practice in applying selfmanagement of the patient with Diabetes Mellitus. A comprehensive search for primary research article was conducted in the databases MEDLINE, Biomed Central, Pub Med, and Google Scholar, published from 20092017. There were 10 journals about self-management in patients with DM. The descriptions were found from the 10 journals, the author divided into four things, namely about perception, education, self-care behavior, and tool of self-management. Self-management for DM patients was necessary in order to control the patient's illness. This happens because self awareness of patients to perform self-management so as to improve the quality of life for patients with DM. Patients should perform self-management of DM correctly and regularly so that it will bring a good impact on the quality of life of the patient. For that we need to make the correct Standard Operational Procedure/ SOP, so that there are directives and clear instructions. Keywords: Self-management, Diabetes Mellitus, Interventions of self-management.